Dilemmas and Challenges in the Development of Urban Metropolitan Areas – the Case of the Cracow Metropolitan Area - Noworól, Aleksander (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The paper presents contradictions related to the process of metropolisation. They consist in the co-existence of certain phenomena, like an improved economic situation and living conditions, but also the consequences of suburbanisation. Against this background, a dilemma emerges that encourages the elaboration of tools for controlling urbanisation processes in suburban areas. Based on the insight into changing approaches to regional policy, the paper presents new instruments for managing urban functional areas. Those instruments depend on social dialogue and multi-sectorial cooperation which, due to the low level of social capital in Poland, are difficult challenges. The paper's final section presents recommendations for Cracow's government in respect of the metropolitan dimension of local development policy.